Linguistisch fundierte Sprachförderung und Sprachdidaktik: Grundlagen, Konzepte, Desiderate - Klages, Hana; Pagonis, Giulio (DaZ-Forschung, 2015)
Knowledge derived from linguistics and language acquisition research is still only sporadically translated to programs for teaching German as a second language. The papers in this collection attempt to bridge the gap between linguistic and educational research about German as a second language and to apply the findings of theoretical and empirical research to develop concrete suggestions for the design of language programs.